Influences of Islamized higher education in developing advertising perception towards Islamic clothing: a conceptual study on young Muslims in Malaysia - Haque, A. K. M. Ahasanul; Abdullah, Kalthom; Ahmed, Faruk (2017)
Perception process that, pivoting on by-born psychological and physical characteristics, depends mainly on personal, stimulus, environmental and situational factors helps human being to convert their attitudinal, learned and behavioral states codified in psychology, sociology, anthropology, and economics disciplines. According to perception theories, Islamized higher education has capability to reshape every Muslim's conventional educationbased perception into Islamic value-based education perception, which fits a specific relationship that creates when Islamic advertising theme changes conventional advertising perception as a result of learning from Islamized higher educational institution. This study, Islamized higher education is multidimensional independent construct that has been possible to be developed based on 'area of Islamization', 'academic Islamization', 'service Islamization', and 'facilities Islamization', which has significant positive effect on Islamic values, social values, and cultural values that are exploited in the conceptual model as mediating variables affecting endogenous variable on Islamic advertising perception towards Islamic clothing. In addition, moderating variable that has been explored on the relationship between Islamized higher education and Islamic advertising perception towards Islamic clothing is the educational background: Islamic or conventional. It can be assumed that Islamic background education would moderate more than that of conventional education if one unit of Islamic or conventional background education increases in an Islamized higher education institution. As a future research, methodological and empirical study can be conducted to advance the Islamic advertising perception theory and practice.